Synthesis of informational network structure for supporting the process of decision making for commanders during the special operations preparing - Rozanova, L. V. (Honor and Law, 2019)
Main conditions of informational supporting are reviewed for military unit commanders of security forces in purpose of rational solutions obtaining during special operations preparing. The solution for informational network structure is proposed for informational-analytical supporting of decision making of commander during the special operations preparing.